ANALISIS NILAI BUDAYA SIRIK NA PACCE DALAM FILM ANAK KARAENG KARYA YUS AMIN DB - Novidayanti; Daeng, Kembong; Yunus, Andi Fatimah (Journal Studies in Indonesian Language and Literature, 2024)
The purpose of this study is to describe the cultural value of sirik na pacce in the movie Anak Karaeng by Yus Amin Db using the theory according to Abu Hamid in this study using observation techniques and document studies. The results of this study indicate that (1) the form of sirik in the movie Anak Karaeng by Yus Amin Db there are three categories of sirik, namely, first sirik pakasirik is sirik related to personal self-esteem, as well as self-esteem or family dignity. The second sirik mappakasirik sirik is a type of sirik related to work ethic. The third sirik tappela' sirik is a person's sense of shame that is lost "disturbed" because of something. (2) The form of pacce in the movie Anak Karaeng by Yus Amin Db based on the cause of the emergence of feelings or encouragement consists of two, namely, the first feeling of pacce because of seeing family or other people affected by disaster. Secondly, feelings of pacce like this sometimes encourage us to provide assistance to that person. The cultural value of sirik na pacce in the movie Anak Karaeng by Yus Amin Db describes the buildings and patterns of life that want to be organized as a custom and culture that provides moral messages. Based on several scane words, sentences, diaglogues that contain the meaning of sirik na pacce that want to be poured and placed in accordance with the attitude in society.